Tinjauan Disiplin Belajar Siswa Tata Kecantikan Rambut pada Mata Pelajaran Produktif di SMKN 7 PADANG - Rahmania, Rahmania; Rostamailis, Rostamailis; Yanita, Merita (Journal of Home Economics and Tourism, 2016)
The background of this study was the aspects related to student discipline in following the productive lessons are still low. This condition is expected to trigger low ability of the students in conducting the practice on the productive subjects. The purpose of this study was to reveal the Discipline Rules of Student Beauty Class in ProductiveLesson at SMK 7 Padang. The type of this research was a descriptive quantitative. The population in this study was all of class X and XI Hairstyling students at SMK 7 Padang totaling 86 students. The sample in the study is the entire population that numbered 86 students (total sampling). The data were obtained using a questionnaire form of Likert scale that has been tested for validity and reliability. Analysis technique used percentages Achievement Level Respondents (TCR). The results showed that; 1) Indicators discipline when going to school and class was 61.87% with a low category, 2) Indicators of student discipline in doing the practice as a whole has percentage 59% with low category so disciplined in complying with the rules in preparation for the practice of 62%, 3) Indicator discipline Work Process Practice 57%, 4) Indicators resolving discipline in practice is still 57%, all in the low category. Discipline in obeying the order at the time of the practice in the laboratory showed that in total amounted to 59%, with a description of the order when you sign laboratory 56% with a low category, obedient discipline when borrowing tools and materials 62% low category, comply with the prohibitions in the laboratory 62 % low category and the Discipline of student learning time out of laboratory 53% with very poor category. It is expected both to the school and the students will enforce discipline in learning. Keywords: Overview, Discipline, Learning, Student, Hairstyling, Lesson Productive.